Pengaruh Kepuasan Kerja Guru di SMP Negeri di Kota Padang Panjang - Febri Yenti (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2015)
This study aims to analyze (1) teachers' perceptions of the principal's leadership significant effect on the motivation of junior high school teachers working in Padang Panjang, (2) perceptions of teachers about the principal's leadership significant effect on labor discipline in junior high school teacher in the city of Padang Panjang, (3 ) Motivation significant effect on labor discipline teachers in secondary schools in the city of Padang Panjang, (4) perceptions of teachers about the principal's leadership significant effect on job satisfaction of teachers at SMP Negeri Padang Panjang, (5) Motivation significant effect on job satisfaction of teachers in junior high school in Padang Panjan, and (6) work discipline teachers significantly influence job satisfaction of teachers in secondary schools in the city of Padang Panjang. Based on this research is that (1) teachers' perceptions of leadership principals have significant and positive impact on work motivation of teachers schools in the city of Padang Panjang, which means that the leadership of the principal duties and the role of teacher motivation in melakanakan duty increases, (2) Influence teachers' perceptions of principal leadership to discipline teachers working in secondary schools in the city of Padang Panjang, meaning the better the leadership of the school principal as the principal menajalankan peranya the teachers more disciplined in carrying out their duties as a teacher, (3) effect of work motivation of teachers to discipline teachers working in secondary schools in the city of Padang Panjang, meaning that the higher the motivation of teachers then automatically work discipline of teachers also increased, (4) influence teachers' perceptions of principal leadership on job satisfaction of teachers at SMP Negeri Padang Panjang, (5) Effect of motivation on job satisfaction of teachers in secondary schools in the city of Padang Panjang, which means that the teachers are satisfied with all the rules and regulations made and regulation principals in making a decision the teachers more satisfied and motivated teachers is increasing and, (6) Effect of labor discipline teachers on job satisfaction of teachers in junior high school in Padang Panjang, which means that the discipline of teachers in carrying out their duties means teachers are satisfied with the provisions made.